5 - Promoting Japan’s National Interest in Africa: A Review of TICAD - Eyinla, Bolade M. (Africa Development, 2018)
The Tokyo International Conference on African Development (TICAD) was launched by Japan in October 1993. Five follow-up Conferences were held in 1998, 2003, 2008, 2013 and 2016 (TICAD II, III, IV, V, and VI). This article challenges the Japanese claim that the TICAD process is a mechanism for focusing global attention and mobilising international support for Africa. Rather, the TICAD process is seen as signifying a shift in Japan’s policy towards Africa, hitherto defined within the context of the Washington Consensus. It is argued that, in the process, Japan is developing an African policy which is directed at serving its national interest.